APLIKASI PENGENALAN PROFESI PEKERJAAN BAGI ANAK USIA DINI BERBASIS AUGMENTED REALITY - Eka Prasetya Adhy Sugara Muhammad Ali Mahmudi Sugeng Wahyudi (RJOCS (Riau Journal of Computer Science), 2017)
Early age is an important time for a child to develop his talents and potential. At this time, generally children learn in Early Childhood Education or PAUD. One of the lesson materials in PAUD is a lesson about various professions as the ideals of the future. Children are being introduced about various professions such as astronauts, doctors, teachers, pilots, police officers, etc.. Teachers introduce these professions by using a picture book. Picture books have limitations, which only show images and text. Augmented reality technology can be used as a medium to introduce various professions by adding 3 dimensional objects on the media book. This study aims to produce application in introduction of the profession based on augmented reality. The resulting application is a medium to help introduce various professions in the form of 3-dimensional visualization for early childhood. The research method adopted the waterfall method consisting of the stage of determining the needs of the application, designing markers and 3-dimensional objects, creating and publishing apk-formatted applications and testing applications on Android-based smartphone devices. The results of the study in the form of application of learning about various professions that can be run by teachers at school and parents at home.